Showcasing Luxury on Social Media: What Are The Effects? An Anomaly among Lecturers - Erwin Kurniawan A.; Dian Wahyuningsih; Dio Darma (Fakultas Seni Rupa dan Desain ITB, 2023)
In almost every job, technological advancement plays a vital role in making it easierfor humans, including social media. Today, there is a diminution of solidarity, which iscontradictory to the “concept of caring”. Users are increasingly indifferent, sometimesselfish, and exaggerate when they come into contact with posts on social media, thustriggering hacking by irresponsible individuals to achieve certain advantages. Thispaper is dedicated to investigating discriminatory actions against lecturers in theFaculty of ABC–University of XYZ who use Facebook and WhatsApp to show off allthe luxuries of life. Through the experimental–qualitative design, the sample invited“social climbing” lecturers who experienced material and non-material losses. Thisstudy describes that respondents who experienced material impacts due to hackingwere more dominant than those who suffered non-material losses. Most judged that thehacking addressed to respondents was triggered by a dominant intensity on social mediarather than going about their daily routines. However, in the long term, lecturers expresstheir attitude toward improving integrity as an academic community. Recognizing thisreality, the practical implications of regulation and lawlessness in cyberspace need to beenforced. In addition, these findings also set the agenda for future studies.